Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

rDNA-mediated multicopy integration and gene dosage quantification system for microbial zeaxanthin biosynthesis - Ruijing Ling; Shuting Hou; Xiangzhao Mao; Francesco Secundo; Wei Zhou; Meiyi Xi; Yang Xiao; Bei Gao (World Journal of Microbiology and Biotechnology, 2026)

Co-cultivation of Nannochloropsis salina and Xanthophyllomyces dendrorhous in mixed medium enhances lipid and antioxidant yields - Carlo Esposito; Elia Lio; Stefano Gandolfi; Gianluca Ottolina; Francesco Secundo (Algal Research, 2025)

Microalgae: versatile microbial factories for natural product synthesis - Elia Lio; Gandolfi Stefano; Jacopo Paini; Carlo Esposito; Martina Dramis; Floriana Basile; Gianluca Ottolina; Francesco Secundo (Phytochemistry Letters, 2025)

Characterization and antimicrobial activity of extracts from microalgae Chlorococcum sp. with green organic solvents - Elia Lio; Martina Dramis; Gianluca Ottolina; Giancarlo Aldini; Francesco Secundo (Phytochemistry Letters, 2025)

Fatty acid profile of lipids from microalgae grown on media with hydrolysed agro-food biowaste - Carlo Esposito; Elia Lio; Giancarlo Aldini; Francesco Secundo (Phytochemistry Letters, 2025)

Molecular modification of a GH84 β-N-acetylglucosaminidase from Streptomyces violascens for synthesis of lacto-N-triose II using whey powder and chitin-derived N-acetyl chitobiose - Zhuoning Cao; Chengqiang Li; Hong Jiang; Francesco Secundo; Xiangzhao Mao (Food Chemistry, 2025)

Efficient expression of OUC-Sb-lip2 in Yarrowia lipolytica and its comprehensive utilization in the enrichment of DHA and EPA from fish oil - Kunpeng Gao; Qi Xin; Hong Jiang; Francesco Secundo; Xiangzhao Mao (Food Chemistry, 2024)

A chitosan-based antibacterial hydrogel with injectable and self-healing capabilities - Rui Chen; Yanan Hao; Secundo Francesco; Xiangzhao Mao; Wen-Can Huang (Marine Life Science & Technology, 2023)
The presence of bacteria directly affects wound healing. Chitosan-based hydrogel biomaterials are a solution as they offer advantages for wound-healing applications due to their strong antimicrobial properties. Here, a double-cross-linking chitosan-based hydrogel with antibacterial, self-healing, and injectable properties is reported. Thiolated chitosan was successfully prepared, and the thiolated chitosan molecules were cross-linked by Ag–S coordination to form a supramolecular hydrogel. Subsequently, the amine groups in the thiolated chitosan covalently cross-linked with genipin to further promote hydrogel formation. In vitro experimental results indicate that hydrogel can release Ag + over an extended time, achieving an antibacterial rate of over 99% against Escherichia coli and Staphylococcus aureus . Due to the reversible and dynamic feature of Ag–S coordination, an antibacterial hydrogel exhibited injectable and self-healing capabilities. Additionally, the hydrogel showed excellent biocompatibility and biodegradability.

Expanding the application range of the κ‑carrageenase OUC-FaKC16A when preparing oligosaccharides from κ-carrageenan and furcellaran - Chengcheng Jiang; Francesco Secundo; Xiangzhao Mao (Marine Life Science & Technology, 2023)
Carrageenan oligosaccharides are important products that have demonstrated numerous bioactivities useful in the food, medicine, and cosmetics industries. However, the specific structure–function relationships of carrageenan oligosaccharides are not clearly described due to the deficiency of high specific carrageenases. Here, a truncated mutant OUC-FaKC16Q based on the reported κ -neocarratetrose (N κ 4)-producing κ -carrageenase OUC-FaKC16A from Flavobacterium algicola was constructed and further studied. After truncating the C-terminal Por_Secre_tail (PorS) domain (responsible for substrate binding), the catalytic efficiency and temperature stability decreased to a certain extent. Surprisingly, this truncation also enabled OUC-FaKC16Q to hydrolyze N κ 4 into κ -neocarrabiose (N κ 2). The offset of Arg 265 residue in OUC-FaKC16Q may explain this change. Moreover, the high catalytic abilities, the main products, and the degradation modes of OUC-FaKC16A and OUC-FaKC16Q toward furcellaran were also demonstrated. Data suggested OUC-FaKC16A and OUC-FaKC16Q could hydrolyze furcellaran to produce mainly the desulfated oligosaccharides DA-G-(DA-G4S) 2 and DA-G-DA-G4S, respectively. As a result, the spectrum of products of κ -carrageenase OUC-FaKC16A has been fully expanded in this study, indicating its promising potential for application in the biomanufacturing of carrageenan oligosaccharides with specific structures.

Response of Salmonella enterica serovar Typhimurium to alginate oligosaccharides fermented with fecal inoculum: integrated transcriptomic and metabolomic analyses - Jiaying Cheng; Mengshi Xiao; Xinmiao Ren; Francesco Secundo; Ying Yu; Shihao Nan; Weimiao Chen; Changliang Zhu; Qing Kong; Youtao Huang; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2023)
Alginate oligosaccharides (AOS), extracted from marine brown algae, are a common functional feed additive; however, it remains unclear whether they modulate the gut microbiota and microbial metabolites. The response of Salmonella enterica serovar Typhimurium, a common poultry pathogen, to AOS fermented with chicken fecal inocula was investigated using metabolomic and transcriptomic analyses. Single-strain cultivation tests showed that AOS did not directly inhibit the growth of S . Typhimurium. However, when AOS were fermented by chicken fecal microbiota, the supernatant of fermented AOS (F-AOS) exhibited remarkable antibacterial activity against S . Typhimurium, decreasing the abundance ratio of S . Typhimurium in the fecal microbiota from 18.94 to 2.94%. Transcriptomic analyses showed that the 855 differentially expressed genes induced by F-AOS were mainly enriched in porphyrin and chlorophyll metabolism, oxidative phosphorylation, and Salmonella infection-related pathways. RT-qPCR confirmed that F-AOS downregulated key genes involved in flagellar assembly and the type III secretory system of S . Typhimurium, indicating metabolites in F-AOS can influence the growth and metabolism of S . Typhimurium. Metabolomic analyses showed that 205 microbial metabolites were significantly altered in F-AOS. Among them, the increase in indolelactic acid and 3-indolepropionic acid levels were further confirmed using HPLC. This study provides a new perspective for the application of AOS as a feed additive against pathogenic intestinal bacteria.

Preparation and characterization of phosphatidyl-agar oligosaccharide liposomes for astaxanthin encapsulation - Hongyan Wu; Haiyang Zhang; Xuehan Li; Francesco Secundo; Xiangzhao Mao (Food Chemistry, 2023)

Application of enzymes as a feed additive in aquaculture - Qingping Liang; Mingxue Yuan; Liping Xu; Elia Lio; Fang Zhang; Haijin Mou; Francesco Secundo (Marine Life Science & Technology, 2022)
Modern aquaculture must be sustainable in terms of energy consumption, raw materials used, and environmental impact, so alternatives are needed to replace fish feed with other raw materials. Enzyme use in the agri-food industry is based on their efficiency, safety, and protection of the environment, which aligns with the requirements of a resource-saving production system. Enzyme supplementation in fish feed can improve digestibility and absorption of both plant- and animal-derived ingredients, increasing the growth parameters of aquacultural animals. Herein we summarized the recent literature that reported the use of digestive enzymes (amylases, lipases, proteases, cellulases, and hemicellulases) and non-digestive enzymes (phytases, glucose oxidase, and lysozyme) in fish feed. In addition, we analyzed how critical steps of the pelleting process, including microencapsulation and immobilization, can interfere with enzyme activity in the final fish feed product.

Enhanced whole-cell biotransformation of 3-chloropropiophenone into 1-phenyl-1-propanone by hydrogel entrapped Chlorella emersonii (211.8b) - Sikandar Khan; Pengcheng Fu; Alessandro Di Fonzo; Irene Marasca; Francesco Secundo (Biotechnology Letters, 2021)

Coating polypropylene surfaces with protease weakens the adhesion and increases the dispersion of Candida albicans cells - Eugenio Spadoni Andreani; Federica Villa; Francesca Cappitelli; Anna Krasowska; Piotr Biniarz; Marcin Łukaszewicz; Francesco Secundo (Biotechnology Letters, 2017)

Immobilized Hydrolytic Enzymes Exhibit Antibiofilm Activity Against Escherichia coli at Sub-Lethal Concentrations - Federica Villa; Francesco Secundo; Andrea Polo; Francesca Cappitelli (Current Microbiology, 2015)